Commodity Terms of Trade : The History of Booms and Busts. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
We compile a historical dataset covering nearly 40 years of booms and busts in the commodity terms of trade of over 150 countries. We discuss the characteristics of these events and their effects on macroeconomic performance and, in particular, compare the most recent commodity-price cycle with its historical precedents.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet